2012
DOI: 10.5720/kjcn.2012.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs Regarding Vegetable Consumption, Self-Efficacy and Eating Behaviors according to the Stages of Change in Vegetable Consumption among College Students

Abstract: The purpose of this study was to examine beliefs, self-efficacy and eating behaviors by the stages of change in vegetable consumption among college students (n = 297). A survey was conducted to examine study variables, and subjects were categorized into three groups based on the stages of change: precontemplation/contemplation stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Expecting a more positive affective effect from having a sufficient vegetable intake will contribute to progression to the M stage, as this effect increases the motivation of a subject to improve vegetable intake. As mentioned above, subjects in the A/M stage in the LPG had high scores in self-efficacy and affective attitude, which suggests that, compared to other factors, self-efficacy and affective attitude can be major influencing factors for increasing vegetable intake in adolescents, which has also been shown in other studies [ 11 13 , 22 ]. In addition, Van Duyn et al [ 23 ] reported that self-efficacy and affective attitudes were the most important factors in increasing the consumption of vegetables and fruit.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Expecting a more positive affective effect from having a sufficient vegetable intake will contribute to progression to the M stage, as this effect increases the motivation of a subject to improve vegetable intake. As mentioned above, subjects in the A/M stage in the LPG had high scores in self-efficacy and affective attitude, which suggests that, compared to other factors, self-efficacy and affective attitude can be major influencing factors for increasing vegetable intake in adolescents, which has also been shown in other studies [ 11 13 , 22 ]. In addition, Van Duyn et al [ 23 ] reported that self-efficacy and affective attitudes were the most important factors in increasing the consumption of vegetables and fruit.…”
Section: Discussionsupporting
confidence: 66%
“…Questions aimed at evaluating the stages of behavioral changes related to vegetable intake were designed based on previous studies [ 13 18 ]. The first question was “Do you eat various kinds of vegetables?.” Subjects who responded “No” were questioned further, as follows; those who responded “No, I do not intend to eat various kinds of vegetables” to the question “Do you intend to eat various kinds of vegetables from now on?” were classified as PC, while those who responded “No, but I am planning on eating various kinds of vegetables in the near future (within six months)” were classified as C, and those who responded “Yes, I will eat various kinds of vegetables very soon (within one or two months)” were classified as P.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Items for assessment of beliefs regarding nutrition label use (i.e., behavioral beliefs) were developed based on responses from pilot study and previous studies [ 24 , 25 ]. These included health and nutritional benefits (e.g., selecting healthy foods, not having foods high in fat or sodium, disease prevention, calorie control, and obesity prevention), practical benefits (e.g., making me eat adequate amount of foods, comparison of foods in food selection, helping others to select good foods), and disadvantages of nutrition label use (e.g., not eating favorite foods, spending time for food selection, cost, restrictions in food choices).…”
Section: Methodsmentioning
confidence: 99%
“…Items for assessment of control beliefs were developed using literature review [ 24 , 25 ] and responses from the pilot study. Fifteen items were used to measure control beliefs.…”
Section: Methodsmentioning
confidence: 99%